Pengembangan Alat Analisis Humor dalam Komik Jepang - Akhmad Saifudin; Yuyu Yohana Risagarniwa; Elvi Citraresmana; Inu Isnaeni Sidiq (Japanese Research on Linguistics, Literature, and Culture, 2019)
The main objective of this study is to develop a theoretical tool to analyze humorelements in Japanese comic (manga). The authors narrow the definition of â€œtoolâ€ as atheoretical framework that can be used in an inductive research. Developing this tool isof importance since evaluating the quality of humor in comic is difficult and subjective,due to the inclusion of humor as a cognitive and cultural product (Hurley et al, 2011).The authors strongly emphasize that this study was a theoretical review one. Weaimed to develop a theoretical foundation pertaining to semiotic analysis in humorousmanga products. To achieve the aim, we applied qualitative content analysis to buildthe foundation inductively. The authors identify that in order to analyze humor inmanga, Bergerâ€™s theory of humor techniques (1976, 1993) can be utilized to explorecomical effect in manga. Furthermore, Wilson and Sperberâ€™s framework (2004) canalso be used to evaluate the context of situation pictured in manga. The former theoryis imperative since it highlights the function of drawing representation to buildhumorous atmosphere, while the latter functions to decode the meaning and purposeof humor created by manga creators. To conclude, a theoretical contribution can bewithdrawn from the discussion in this study. However, to really measure Japaneseâ€™scognitive and cultural values of humor expression, further application of this analysistool needs to be established in a wider and more comprehensive set of data.